2013
DOI: 10.3389/fpsyg.2013.00426
|View full text |Cite
|
Sign up to set email alerts
|

Imagined motor action and eye movements in schizophrenia

Abstract: Visual exploration and planning of actions are reported to be abnormal in schizophrenia. Most of the studies monitoring eye movements in patients with schizophrenia have been performed under free-viewing condition. The present study was designed to assess whether mentally performing an action modulates the visuomotor behavior in patients with schizophrenia and in healthy controls. Visual scan paths were monitored in eighteen patients with schizophrenia and in eighteen healthy controls. Participants performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, sev eral studies have reported that the restricted scanning found in individuals with schizophrenia on passive viewing tasks nor malized in active viewing conditions. [27][28][29] As participants were given a task in the present study, the more centre looking strat egy found in individuals with schizophrenia may better reflect a difference in multiple object tracking ability than a restricted scanning ability. Yet another possibility is that their centre looking strategy is a consequence of a decreased ability to de tect and/or to represent agents.…”
Section: Discussionmentioning
confidence: 82%
“…However, sev eral studies have reported that the restricted scanning found in individuals with schizophrenia on passive viewing tasks nor malized in active viewing conditions. [27][28][29] As participants were given a task in the present study, the more centre looking strat egy found in individuals with schizophrenia may better reflect a difference in multiple object tracking ability than a restricted scanning ability. Yet another possibility is that their centre looking strategy is a consequence of a decreased ability to de tect and/or to represent agents.…”
Section: Discussionmentioning
confidence: 82%
“…Impaired eye movements are a well replicated finding in patients with schizophrenia, for a review see Levy et al ( 1994 ) and Trillenberg et al ( 2004 ). For example, scanpaths during exploratory eye movements are spatially limited and contain fewer fixations in patients with schizophrenia (Loughland et al, 2002 ; Minassian et al, 2005 ; Bestelmeyer et al, 2006 ; Benson et al, 2007 ; Nishiura et al, 2007 ; Takahashi et al, 2008 ; Suzuki et al, 2009 ; Elahipanah et al, 2011 ; Delerue and Boucart, 2013 ; Sprenger et al, 2013 ). When following a moving target, smooth-pursuit eye movements are impaired (Schwartz et al, 1995 ; Nkam et al, 2001 , 2010 ; Nagel et al, 2012 ; Krishna et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The final papers in this section cover topics related to motion processing, eye movements, temporal context processing effects and time perception. These include studies of: 15–17) biological motion perception in schizophrenia (Hastings et al, 2013 ; Kim et al, 2013 ; Spencer et al, 2013 ); (18–19) eye movement and scan pattern abnormalities (Delerue and Boucart, 2013 ; Sprenger et al, 2013 ); (20) visual and motor disorganization (Giersch et al, 2013b ); (21) oscillatory markers of abnormal temporal context processing (Dias et al, 2013 ); and (22) the role of impaired temporal processing in visual processing abnormalities in schizophrenia (Giersch et al, 2013a ).…”
mentioning
confidence: 99%